Occupational well-being and leadership in a school community. Issue 1 (3rd January 2017) - Laine, Sari; Saaranen, Terhi; Ryhänen, Eva; Tossavainen, Kerttu
Abstract : Purpose: The purpose of this paper is to present well-being, leadership, and the development of each from a communal perspective in a Finnish primary school in the years 2000-2009. Design/methodology/approach: The study included five sets of data. The quantitative research data were collected from the school staff using the Well-Being at Your Work index questionnaire in 2004 ( n =36), 2005 ( n =41), and in 2009 ( n =34). In 2006, two group interviews were carried out with the school personnel ( n =21), and in 2011, retrospective interview data were collected from an expert classroom teacher ( n =1). Quantitative data were analysed statistically using descriptive statistics. The qualitative group interview data were analysed by an inductive content analysis, while the expert interview was analysed according to the methods of factual analysis. Findings: During this period, several communal interventions were developed in the school to promote occupational well-being. Over the course of the study, staff members' satisfaction with the actions and the support provided by the principal has improved, and leadership-related problems have decreased. Research limitations/implications: The results cover research findings from one school and therefore cannot be generalised to other Finnish school communities. Originality/value: Schools' work communities must be active in developing interventions to improve their own occupational well-being. Furthermore, leaders must be actively involved in the development of occupational well-being.